Plano de segurança do paciente para pacientes com sistemas de estimulação encefálica profunda submetidos a exames de imagem por ressonância magnética no Hospital Marcelino Champagnat - Ramos, Maria Manuela de Andrade e Silva (2016)
In 2013, the National Program Patient Safety (PNSP) was implemented in Brazil through Resolution RDC 36, providing that the Brazilian health institutions must have a Patient Safety Plan (PSP) for situations that may lead to adverse events (AEs), which are unintentional injury or damage caused to the patient by the health care intervention and not by the primary disease. The PSP is a document with scientific basis that points to hazardous situations and describes strategies and actions defined by the health service for risk management in order to prevent and reduce AEs in all phases of patient care. Implantation of Deep Brain Stimulation (DBS) devices is considered a routine procedure at the Hospital Marcelino Champagnat (HMC), located in Curitiba – PR, and it consists in a practice widely used to improve symptoms and quality of life of patients with certain chronic neurological disorders.The reliability and accuracy of the final brain positioning of the leads, after the DBS implantation are of paramount importance to assure efficacy. Currently, post-operative Magnetic Resonance Imaging (MRI) is the gold standard for the documentation of the correct lead positioning. However, the interaction between the DBS system and the MRI radiofrequency field could represent an important source of adverse events (EAs) since it allows electric currents induction with potential to cause local thermal injuries on high resistance sites. The safety recommendations from the DBS system manufacturers for most of the already deployed systems are quite restrictive resulting in long examination times or low quality images, which compromises the practice in many centers. Thus, the present work proposes the development of a PSP based on the manufacturer's safety recommendations and a systematic review of the literature to the specific situation of patients with DBS systems undergoing MRI scans at the HMC. We found a total of 26 papers, that were considered relevant and allowed us to identify the potential sources of risk in order to avoid them, collaborating to the successful elaboration of the PSP. Besides supplying local demand, this work also aims to promote patient safety and draw attention to the need of interposing barriers in order to avoid significant AEs situations that a radiology department may be presented with. Moreover, the methodology proposed here can serve as a basis for other imaging centers to compose their own PSPs.